Efektivitas Akupresur Terhadap Dismenore Pada Remaja - Husnul Khotimah (Akademi Kebidanan La Tansa Mashiro, 2021)
One of the complaints during menstruation is dysmenorrhea. The treatment of dysmenorrhea so far has been more to the provision of pharmacological therapy, but rarely uses phytopharmaceuticals such as acupressure. The purpose of this study was to analyze the effectiveness of acupressure to treat dysmenorrhea pain in adolescents. This type of research is a quantitative research type Quasi Experiment with pre-test post-test One Group Design. The population of this study amounted to 185. The sampling technique used a non-probability sampling approach (saturated sampling). Determination of the number of samples in this study using calculations from Sastroasmoro Ismael with a sample size of 26. Before the intervention, a pre-test was given in the form of an assessment of the dysmenorrhea pain scale, then the researchers intervened in the treatment group by doing acupressure therapy, after that a post-test was carried out to measure Dysmenorrhea pain scale whether there is a difference or not. Data analysis using Wilcoxon Signed Rank. The results of statistical analysis showed that the value (p = 0.000) so it can be concluded that acupressure is effective for reducing dysmenorrhea. The acupressure given will make the respondent relax and increase immunity